KONSEP MASKULIN DALAM KARYA METROPOP ANTOLOGI RASA KARYA IKA NATASSA (Masculine Concept in Popular Literature Novel Antologi Rasa by Ika Natassa) - Diah Meutia Harum (SAWERIGADING, 2018)
Patriarchal order is a form of community system with men as the head of the family which has power to control and become a dominant individual. Male dominance is an ever-present concept in a society even though women’s movement challenges this idea by demanding recognition and identity. Novel Antologi Rasa is one of metropop genre work (such as chicklit, teenlit, etc.) that presents the life of modern society.This research would like to explore how the masculine concept is voiced through the perspective of female authors by means of novel’scharacter. The method used is literature review with reading technique and record technique. The theory used is the theory of naratology by looking at the fokalization voiced figures. In this novel, it is found that the modern world which becames the background of this story does not make this novel free from masculine domination, yet it has become the scheme of thought of female characters in this novel.AbstrakTatanan patriarki merupakan bentuk sistem masyarakat dengan laki-laki sebagai kepala keluarga memiliki kekuatan untuk mengendalikan dan menjadi individu yang dominan. Dominasi laki-laki adalah konsep yang selalu ada di masyarakat walaupun gerakan perempuan menantang gagasan ini untuk menuntut pengakuan dan jati dirinya. Novel Antologi Rasa adalah salah satu karya bergenre metropop (seperti chicklit, teenlit, dll) yang menyajikan kehidupan masyarakat modern dengan gaya hidup serba boleh. Penelitian ini hendak melihat bagaimana konsep maskulin disuarakan lewat perspektif pengarang perempuan melalui penokohannya. Metode yang digunakan adalah kajian literature dengan teknik baca dan teknik catat. Teori yang digunakan adalah teori naratologi dengan melihat fokalisasi yang disuarakan tokoh-tokohnya. Dalam novel ini dihasilkan, dunia modern yang menjadi latar belakang penceritaan ini tidak membuat novel ini terbebas dari dominasi maskulin yang menjadi skema pemikiran dari tokoh perempuan dalam novel ini.